Ecotheology as a pathway to economic empowerment for survivors of violence against women and children: Evidence from dayah diniyah darussalam - Mellyan, Mellyan; Junaidi, Junaidi (Jurnal Anifa: Studi Gender dan Anak, 2025)
Dayah Diniyah Darussalam has provided a safe house for survivors of violence. This dayah, led by Teungku Inong, has consistently protected women and children who are victims of violence since 2000. Now the dayah has begun implementing ecological-based activities. The purpose of this study is to determine how the system of empowering women and children who are victims of violence with an ecotheological approach in Dayah Diniyah Darussalam. This study uses a qualitative method with a Descriptive Analysis approach. Data collection is carried out using observation, interviews and documentation searches. The results show that the ecotheological program at the Darussalam Diniyah dayah has been running since 2024. However, long before that, the Teungku at the dayah had provided study materials on ecotheology, environmental fiqh and the like. There is a program called Meulampoh Aneuk Beut ue Dayah (Meutuah). There are five Meutuah programs, namely Vegetable Gardening, Catfish Cultivation, Honey Cultivation, Bamboo Crafts and Waste Processing. However, there are still obstacles to implementing ecotheology-based dayah. First, some communities perceive dayah as a place for growing vegetables, not for reciting the Quran. Second, the Tengku Inong (indigenous people) still perceive negative views toward the program, even from highly educated individuals. Third, the environmental fiqh curriculum at Dayah Diniyah Darussalam has not yet been implemented. Fourth, government guidance and direction are still needed to realize ecotheology-based dayah. Keywords: Dayah Diniyah Darussalam, Ecotheology, Violence, Economy, Women and Children